Apocalypse man the death drive and the rhetoric of white masculine victimhood - Kelly, Casey Ryan 1979- (The Ohio State University Press, 2020)
"Examines white masculine victimhood by looking at the rhetoric of gender-motivated mass shooters, white supremacists, online misogynist and incel communities, survivalists and doomsday preppers, gun culture and political rallies, and political demagogues"--